Fear of retaliation and citizen willingness to cooperate with police - Papp, Jordan (Policing and society, 2019)
Qualitative research has shown that fear of retaliation influences an individual’s willingness to cooperate with the police. This research has shown that those who are fearful of being retaliated against are less likely to cooperate with the police (Clayman, C. and Skinns, L., 2012. To snitch or not to snitch? An exploratory study of the factors influencing whether young people actively cooperate with the police. Policing and society: an international journal of research and policy, 22 (4), 460-480; Rosenfeld, R., Jacobs, B., and Wright R., 2003. Snitching and the code of the street. British journal of criminology, 43, 291-309; Whitman, J. and Davis, R., 2007. Snitches get snitches: youth, gangs, and witness intimidation in Massachusetts. Washington, DC: National Center for Victims of Crime). This study examined this topic quantitatively so as to gain an understanding of the influence of fear of retaliation relative to other known correlates of cooperation with the police. Data for this study were collected from 408 Detroit households from 3 different neighbourhood clusters. Results indicated that fear of retaliation reduces an individual’s willingness to cooperate with the police. However, even more salient was trust in the police, which showed that citizens who are more trustful of the police report greater willingness to cooperate with them.